Guidelines for Developing Personnel Potential of Local Government Organizations Case Studies in Muang Phitsanulok District Phitsanulok Province - Chanidthai, Kritwarit; Bodeerat, Chot (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the approach to the development of personnel, and local government organizations, 2) to study the performance of local government personnel, and 3) to factors affecting the development of personnel. and 4) to study the approach to the development of personnel, local government organizations Case Studies in Mueang Phitsanulok District, Phitsanulok Province Defines a sample to represent the population, namely, the personnel of the local administrative organization. 350 cases in Phitsanulok district, Phitsanulok province, using Taro Yamane’s formula at a 95% confidence level. The research tools are questionnaire and interview. Described statistics are distributed in the form of frequency, percentage, average, and standard deviation. Inference statistics The statistics used in test analysis are t-test, F-test, and Multiple Regression Analysis. The results of the study were as follows: 1) The respondents expressed their opinions. level of the development of personnel, and local government organizations the overall average was at a high level. 2) the performance of local government personnel, there was a high average and 3) The factors affecting the personnel potential development approach were found that personal factors Work experience Different Affecting the guidelines for the development of personnel potential of local government organizations difference was statistically significant at the .05 level. and the competency of the personnel of the local government organization, overall, affected the guidelines for the development of personnel potential of local government organizations. Case studies in Muang Phitsanulok District Phitsanulok Province In the same direction were statistically significant at a level of .05. 4) There are 4 guidelines for developing the personnel potential of the local government organization, namely, approach 1. Design according to the needs of personnel with different personal factors, approach 2. Human resource management and management Guideline 3. Development or improvement of development methods and approaches 4. Development monitoring